(Shared) ethnicity in ethnographic research on clandestine and informal practices in the migrant and ethnic minority economy: Methodological and ethical challenges. (14th May 2022) - Hiah, Jing
Abstract : This article addresses the methodological and ethical challenges of ethnographic research on sensitive topics such as clandestine practices in the migrant and ethnic minority economy. Drawing on related criminological and sociology of deviance literature I draw on my experiences of insider-ethnographic research in the Chinese migrant and ethnic minority economy in the Netherlands and Romania to demonstrate how stigmas related to race/ethnicity and clandestine practices can strongly shape access, rapport and researcher's positionality in the field. Research participants' concerns about these stigmas also revealed ethical questions on how to report on clandestine and informal practices without contributing to further stigmatisation and racialisation. At the same time, my experiences show that whether clandestine practices and race/ethnicity are considered sensitive topics is an emergent issue. In the Netherlands, due to active enforcement of clandestine practices in the migrant and ethnic minority economy, these practices were a sensitive topic of inquiry. In Romania, by contrast, clandestine practices were not treated as sensitive subject matter as these were normalised by research participants and broader Romanian society, due to a lack of active enforcement and criminalisation.